Knights vs. the end (of everything) - Phelan, Matt 1970- (Greenwillow Books, an Imprint of HarperCollins Publishers, 2020)
"The four daring knights and one intrepid archer enter the Faerie Realm, where they find dangerous warlocks, a mysterious knight, and one very nasty dragon"--
Keywords: Ritter; Fantastischer Roman; Drachen; Abenteuer; Knights and knighthood / Juvenile fiction; Characters and characteristics in literature / Juvenile fiction; Knights and knighthood / Fiction; Characters in literature / Fiction; Adventure and adventurers / Fiction; Fantasy; Humorous stories; JUVENILE FICTION / General; Characters and characteristics in literature; Knights and knighthood; Children's stories; Action and adventure fiction; Fantasy fiction; Fiction; Humorous fiction; Juvenile works; Kinderbuch